Chapter 5: Treatment Principles (Principles of Medical Toxicology, 2025)
AuthorProf. Dr. Suresh V Chennupati, Principal and Professor, Chennupati Indo-American School of Pharmacy, Andhra Pradesh, IndiaAbstractManagement of toxic exposures follows systematic principles aimed at reducing further absorption, enhancing elimination, administering specific antidotes when available, and providing supportive care. Gastrointestinal decontamination methods include activated charcoal, which adsorbs many toxins but is contraindicated for caustic ingestions, hydrocarbons, and patients with unprotected airways. Once widely used, gastric lavage and induced emesis now have limited roles due to efficacy and safety concerns. Whole bowel irrigation may benefit in specific scenarios like sustained-release medication or body packer ingestions. Antidotal therapy directly counteracts toxic mechanisms through various actions including receptor antagonism, chelation, substrate competition, and metabolic interventions. Well-established antidotes include N-acetylcysteine for acetaminophen, naloxone for opioids, and various chelating agents for heavy metals, though many poisonings lack specific antidotes. Supportive care forms the cornerstone of management for most exposures, focusing on maintaining vital functions, treating symptoms, and preventing complications. Enhanced elimination techniques—including multiple-dose activated charcoal, urinary alkalinization, and extracorporeal methods like hemodialysis—can significantly reduce toxin burden for selected substances with appropriate pharmacokinetic properties. Treatment decisions must balance potential benefits against risks while considering individual patient factors including age, comorbidities, and exposure characteristics.Keywords: Decontamination, Antidotes, Activated Charcoal, Enhanced Elimination, Hemodialysis, Supportive CareVIEW PDF